Resina composta indireta como alternativa funcional e estética em reabilitações protéticas - Reis, José Maurício dos Santos Nunes [UNESP]; Jorge, Érica Gouveia; Silva, Regina Helena Barbosa Tavares da; Segalla, José Cláudio Martins; Faria, Ivan Ribeiro de; Pinelli, Lígia Antunes Pereira (My University, 2012)
Due to mechanical and aesthetic improvement properties, continuous fiber-reinforced composites have been developed to replace the metal framework in fixed partial dentures becoming an interesting alternative to conventional treatments. A male patient, 57 years old, attended at Fixed Partial Denture Clinic of Araraquara Dental School - UNESP, complaining about upper right first molar absence. After clinical examination, it was observed: upper right second molar with amalgam restoration and periodontal bone reduction and upper right second premolar unsatisfactory treated. Following the clinical conditions and the patient expectations, it was decided to use a fiber-reinforced composite resin to make a three-element fixed bridge. The patient showed full satisfaction with the aesthetic and functional results. The case has been followed up for 60 months.

Devido à melhoria nas propriedades das resinas compostas indiretas, principalmente quando associadas com fibras de reforço, esse material tornou-se mais uma alternativa para os procedimentos reabilitadores. Um paciente, 57 anos, compareceu à Clínica de Prótese da Faculdade de Odontologia de Araraquara, queixando-se da ausência do primeiro molar superior direito. Após exame clínico, verificou-se diminuição no periodonto de suporte do segundo molar superior direito, restaurado com amálgama e segundo pré-molar superior direito reabilitado insatisfatoriamente. De acordo com as condições clínicas e os anseios estéticos do paciente, foi confeccionada uma prótese parcial fixa de 3 elementos, utilizando resina composta indireta com fibras de reforço. O paciente demonstrou-se plenamente satisfeito com o resultado estético e funcional obtido. O caso encontra-se em proservação há 60 meses.
Indirect composite resin as functional and aesthetic alternative in dental prosthesis
Keywords: Dental prosthesis; Composite resins; Mouth rehabilitation; Prótese parcial fixa; Resinas compostas; Reabilitação bucal